ANALYSIS OF CAPITAL BUFFER, BOARD GENDER DIVERSITY, OWNERSHIP CONCENTRATION, AND INDEPENDENT COMMISSIONERS ON BANK STABILITY - Hendra, Hendra; Setijaningsih, Herlin Tundjung (International Journal of Application on Economics and Business, 2025)
The objective of the research is to examine the impact of capital buffer, board gender diversity, ownership concentration, and independent commissioners on the stability of Indonesian banks. Data was obtained from the Financial Services Authority's (OJK) website, with a particular emphasis on commercial banks from 2019 to 2023. The study encompasses 14 listed commercial banks that are classified as KBMI 3 and KBMI 4, except for Sharia Banks. Z-Score is the dependent variable used to measure bank stability, and the independent variables are capital buffer, ownership concentration, gender diversity on the board, and independent commissioners. The results suggest that the capital buffer has a substantial positive effect on the stability of Indonesian banks. A sufficient capital buffer can echance the confidence of clients and investors in the bank's stability, potentially improving its market value and financial performance. Results show that ownership concentration demonstrates negative and insignificant effects on bank stability. Conversely, board gender diversity and independent commissioners shows a positive and insignificant correlation with bank stability. The study recommends strengthening the role of independent commissioners and advancing gender diversity. Regulators are advised to enforce governance standards and oversee ownership structures. Additionally, the findings support stricter capital requirements to enhance banking sector stability.